Pencatutan Aparatur Sipil Negara dan TNI-POLRI Dalam Keanggotaan Partai Politik - Muhammad Ardiyansyah; Febria Mutiara Hanifa; Rifqi Maqbullah Murtadho; Roberto Simbolon (Universitas Kristen Satya Wacana Salatiga, 2024)
This article discusses legal issues regarding the inclusion of PNS and TNI/POLRI in political party membership. The inclusion of the State Civil Apparatus and TNI/POLRI in Political Party Membership is discussed because the State Civil Apparatus and TNI/POLRI are prohibited from becoming members and/or administrators of political parties. Based on the results of a review of the administrative verification process and factual verification of political party member candidates for the 2024 election in Salatiga City, it was found that the names of civil servants and the TNI/POLRI were included in the membership of political parties. parties through SIPOL (Political Party Information System).